2005
DOI: 10.1038/sj.cr.7290368
|View full text |Cite
|
Sign up to set email alerts
|

Chinese NGOs in action against HIV/AIDS

Abstract: Chinese nongovernmental organizations (NGOs) have played a significant role in the battle against AIDS in the People's Republic of China. This article provides a brief overview of the structure of these organizations, as well as an analysis of their principle accomplishments. Of great significance in this analysis is the fact that Chinese NGOs have effectively dealt with many sensitive health education areas that government authorities have felt reluctant to handle directly. As such, they have provided an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Policies should also be made at the societal level to enhance social support towards PLWH, to improve their psychological well-being (e.g., less depressive symptoms, less anxiety) and health-related behaviors (e.g., active coping, medication adherence, regular check-up). Policies should not only be made for the formal health care institutions (e.g., hospitals, centers for disease control and prevention (CDCs)), but also for non-governmental organizations (NGOs) that have played an important role in HIV prevention and patient care (e.g., health education, behavioral intervention, and care for PLWH) [52, 53]. Many NGOs are not officially registered and acknowledged in China even though some of them are working for the government (e.g., CDCs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Policies should also be made at the societal level to enhance social support towards PLWH, to improve their psychological well-being (e.g., less depressive symptoms, less anxiety) and health-related behaviors (e.g., active coping, medication adherence, regular check-up). Policies should not only be made for the formal health care institutions (e.g., hospitals, centers for disease control and prevention (CDCs)), but also for non-governmental organizations (NGOs) that have played an important role in HIV prevention and patient care (e.g., health education, behavioral intervention, and care for PLWH) [52, 53]. Many NGOs are not officially registered and acknowledged in China even though some of them are working for the government (e.g., CDCs).…”
Section: Discussionmentioning
confidence: 99%
“…Many NGOs are not officially registered and acknowledged in China even though some of them are working for the government (e.g., CDCs). In addition, financial investments on NGOs should be increased and engagement of NGOs to HIV/AIDS prevention and care for PLWH should be encouraged [52, 53]. At individual level, psychological counseling and interventions are needed to reduce individuals’ internalized stigma, depression, and suicidal ideation, and to improve mental health status and quality of life of PLWH [5457].…”
Section: Discussionmentioning
confidence: 99%
“…MSM-serving CBOs may be a strategic ally in the mission to reach the population, as they are well established hubs with access to the demographic. 4,20,21 Their participation might be advantageous for improving the implementation of interventions targeting the sexual partners of HIV-infected MSM.…”
Section: Introductionmentioning
confidence: 99%
“…The current study found that PLWHA generally obtained more support from the relatives, friends, and neighbors than service providers. Healthcare professionals are cited as caring for PLWHA in these cities [2,5,46], but the current study found that the number of ties to service providers was small and the strength was weak. Some researchers believe that actual social support may not be helpful unless it is perceived to be support by PLWHA [22], which underlines the importance of support being perceived.…”
Section: Discussionmentioning
confidence: 57%
“…The Chinese government has developed supportive policies and programs including the ''Four Free and One Care'' program in 2003, dedicated to decreasing economic barriers and increasing access to antiretroviral therapies for people with HIV; establishing the State Council AIDS Working Committee in 2004; creating the AIDS Prevention and Control Regulations in 2006 [2]; and the shifting of resources to social development and public health programs since the SARS outbreak [3]. In recent years, traditional taboos pertaining to sex have diminished [4]; many types of media have been used for condom promotion; several Chinese celebrities in literature and art have served as goodwill ambassadors [5]; and top leaders have made gestures and commitments to endorse HIV/AIDS policy implementation in China [2,4,6].…”
Section: Introductionmentioning
confidence: 98%